(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2026)
This paper explores the integration of classical yogic practices as a holistic intervention for mental health within the contemporary clinical landscape. Anchored in Patanjali’s foundational definition of Yoga as chitta-vritti-nirodha (the cessation of the fluctuations of consciousness), the study examines how the ancient “Eight Limbs” framework addresses modern psychological pathologies, including anxiety, depression, and PTSD. By synthesizing traditional philosophical insights with modern neurobiological findings, the research highlights the efficacy of Yoga in regulating the Autonomic Nervous System (ANS) and the Hypothalamic-Pituitary-Adrenal (HPA) axis. Specifically, the paper reviews evidence regarding the increase of Gamma-aminobutyric acid (GABA) levels and the reduction of serum cortisol through rhythmic breathing (Pranayama) and physical postures (Asana). Furthermore, the study addresses the transition of Yoga from a spiritual discipline to a “top-down” and “bottom-up” therapeutic tool, emphasizing its role in fostering emotional regulation and cognitive space. Despite the documented benefits, the paper identifies critical challenges, including the commercial dilution of the practice and the necessity for trauma-informed, standardized clinical protocols. It concludes that a multi-dimensional, integrative approach—merging the subjective wisdom of the Yogasutras with objective scientific rigor—is essential for addressing the global mental health crisis. Ultimately, Yoga is presented not merely as a complementary therapy, but as a vital self-regulatory strategy for achieving holistic well-being in an increasingly fragmented modern era.